Significance of C-Reactive Protein in Patients with ST-Elevation Myocardial Infarction Over Non-ST-Elevation Myocardial Infarction - Anum, Shahzadi; Khan, Javed Ahmad; Siddiqi, Fuad Ahmad; Asmat, Faryal (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the use of C-reactive protein in patients with STEMI and NSTEMI to differentiate between the type of myocardial infarction at our hospital.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital, Rawalpindi and Armed Force Institute of Cardiology & National Institute of Heart Disease, from Mar 2020 to Feb 2022.Methodology: Patients diagnosed with MI by a consultant cardiologist were included in the study. They underwent all baseline investigations, including C reactive protein, at the time of presentation to a cardiac emergency. The treating consultant diagnosed MI (ST elevation or non-ST elevation) based on electrocardiogram findings. Values of C reactive protein and other socio-demographic variables were compared in both groups (patients with and without ST elevation MI).Results: A total of 3500 patients with myocardial infarction were included in the final analysis. 2219(63.4%) had NSTEMI,while 1281(36.6%) had STEMI. Statistical analysis showed that C-reactive protein levels were not statistically different in both groups (p-value-0.375), but gender and Creatinine kinase myocardial bound levels were different in patients with non-ST elevation myocardial infarction and ST-elevation myocardial infarction (p-value